Exploring the Islamic principles on leadership and its implementation between Muslim leaders in Sweden - ALABED, MOHAMMAD (My University, 2017)
Leaders’ personality and behavior is formed from accumulated experiences and knowledge that is highly influenced by culture or religious beliefs. This research focuses on the effect of Islamic belief on Muslim leaders’ behavior. It studies the Islamic principles on leadership that are found in the sources of Islamic scripture; Quran and Sunnah, as it is understood by various Muslim authors. The aim is to explore the Islamic perspective on leadership and differences in leadership practice between "practicing" Muslim leaders. This part of the research is based firstly on literature review followed by interviews with Muslim leaders living in Gothenburg, both in profit and non-profit organizations. This research also compares the Islamic leadership approach with similar leaderships approaches found in western literatures which is based on a literature review. After conducting the interviews, it was found that there are notable differences in leadership practice depending on whether the team members are paid or volunteers, the latter group complied more with Islamic teachings. Almost all of the interviewees said that being in a secular country had not been a problem for them. It's found both in literature and interviews that Islamic teaching endorses any practice that a leader may find good as long it does not contradict basic Islamic values. It is also found that the two western leadership theories (transformational leadership and servant leadership) have many similarities with Islamic Leadership
Keywords: Samhällsbyggnadsteknik; Civil Engineering